Calvino tra i macedoni e in macedone - Karanikikj Josimovska, Jovana; Gjurcinova , Anastasija (Incontri. Rivista europea di studi italiani, 2024)
Calvino among the Macedonians and in Macedonian:A story of inspiration and inventionThis article discusses how interest in Italo Calvino developed and how reading his works and criticism influenced the literary environment in Macedonia. The first part of the article provides insight into Italian-Macedonian literary relations and the reception of Italian literature in the Macedonian context, including Calvino’s work. The second part presents a chronological overview of the translations of Calvino's works into Macedonian and the essays published on the subject. Additionally, the article dedicates a section to the results of the conference organized on the anniversary of the writer’s birth. The conclusion summarizes the quantitative data, observations, and comments drawn from various discussions and tributes to Calvino’s work.